Analisis Penerapan Taksonomi Bloom dalam Pembelajaran Siswa Kelas VI SD Negeri 105293 Medan Estate - Suyit Ratno; Riska Sri Pratiwi Tambunan; Delima Situmorang; Karina Sitorus; Nadia Grace Sianturi; Najwa Arisha Putri; Stevy Amelia Manurung; Wahyu Gusnanda Siburian (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Taxonomy is a grouping of objects or materials with certain characteristics. This taxonomy is divided into six levels which include: knowledge, understanding, application, analysis, synthesis, and evaluation. This study aims to analyze the application of Bloom's Taxonomy in grade 6 of SDN 105293 Medan Estate. This study uses a qualitative descriptive research method. Data collection was carried out using interview and observation guidelines. Data analysis was carried out in stages, data reduction, data presentation and drawing conclusions. The results of the study showed that teachers had applied Bloom's Taxonomy to the highest cognitive domain, namely C6. The application of Bloom's Taxonomy in learning at SDN 105293 Medan Estate provides deep insight into how this strategy is applied in the context of grade VI education.